Preliminary results of the combined production of duckweed Spirodela polyrhiza and common carp (Cyprinus carpio) in an aquaponic system - Molnár, Péter; Lelesz, Judit Éva; Kertész, Attila; Bereczki, Gábor; Fehér, Milán (Acta Agraria Debreceniensis, 2023)
As a result of population growth, increasin amount of food is needed, and agriculture is under an increasing burden to meet these needs. Traditional agriculture is often attacked due to its environmental impact. We must find alternative, environmentally friendly ways to produce more food. Aquaponics is a closed system in which we can produce both fish and plants at the same time. Duckweed species are small, aquatic, floating plants belonging to angiosperms. It can potentially be an alternative protein source, due to its high protein content, good amino acid supply, and rapid growth. Under suitable conditions, it doubles its weight in 2–4 days, and can reach a yield of 30 t ha-1 year-1in dry matter. It forms a carpet on top of the water and can be found in slow-moving or still waters. Since they are resistant to a wide range of nutrient concentrations, they are also suitable for cleaning wastewater (such as eutrophicated lakes, sewage reservoirs, liquid manure storage). Fish feed is the primary nutrient source for aquaponic systems, which usually contains fishmeal. If duckweed can be used as an alternative for fishmeal in the feed, it could improve the sustainability of the aquaponic and aquaculture systems. In this study, the aim was to develop an optimal harvesting protocol for duckweed Spirodela polyrhiza under aquaponic conditions. In a four weeks experiments, four harvesting protocols were set up, a control where only biomass measurements were made, a 25% group where 25% of the biomass at the time of measurement was harvested, and a 50% and a 75% group where at the time of measurement 50% and 75% of the biomass was harvested. Three replicates were used per treatment. We weighed the biomass every week and removed the amount corresponding to the group. Based on the preliminary results, it can be said that more biomass was obtained in the groups with the 25% harvesting protocol and the control group.